GARANTIA METROLÓGICA NA MEDIÇÃO DE VOLUME: UMA PRAPOSTA DE METODOLOGIA DE ATUAÇÃO - Silva, Mauricio Evangelista da (2004)
Considerable part of the commercial activities involves the volume measurement as an essential element in these relations. In this context are the alimentary gender, the natural resources: water, natural gas; petrochemical industry derivates, which drive a relevant part of the national economy. Therefore it is essential to assure the metrological confidence as a means to assure fair trade.. With this in mind, the present dissertation has the objective to develop a methodology of acting for the legal metrology activities, concerning to the metrological control of measurements instruments and of materialized measurements for volume. For this it was taken as a basis, the legal requirements relevant to the activities of the Legal Metrology Directory, responsible for this control in the national territory, and the technical metrological prescriptions established in the recommendations of the International Organization of Legal Metrology. At first it was needed to evaluate the state of the art concerning to metrological confidence in this field of interest. Then it was identified the need of a uniformity at national level and an international compatibility relative to the constructing aspects and to the methods and procedures for calibration of the standards of volume currently used. For that matter it was developed and implanted a project featuring: metrological regulations; establishment of a traceability chain; laboratory intercomparisons; and of evaluation of technical competence of the bodies of the RBMLQ, which are involved in the calibration of materialized volume measurements, in the field of legal metrology.